2019
DOI: 10.1089/hum.2019.143
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Relevance of Pre-Existing Anti-Adeno-Associated Virus Immunity in the Context of Gene Therapy for Crigler–Najjar Syndrome

Abstract: Adeno-associated virus (AAV) vector-mediated gene therapy is currently evaluated as a potential treatment for Crigler-Najjar syndrome (CN) (NCT03466463). Pre-existing immunity to AAV is known to hinder gene transfer efficacy, restricting enrollment of seropositive subjects in ongoing clinical trials. We assessed the prevalence of anti-AAV serotype 8 (AAV8) neutralizing antibodies (NAbs) in subjects affected by CN and investigated the impact of low NAb titers (<1:5) on liver gene transfer efficacy in an in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 48 publications
0
35
0
1
Order By: Relevance
“…Overall, 20–40% of candidates for intravascular AAV gene therapy are not eligible due to the presence of NAbs to the vector capsid resulting from cross-reactivity after natural exposure to WT-AAV. 125 To date, it has been challenging to compare the efficacy of a given serotype across distinct studies due to a lack of normalization of the assays as most are developed “in house.” Potential modifiers of the rates/titers of NAbs could include (1) reporter gene, (2) assay technique whether neutralizing assays, non-neutralizing antibody assays (ELISA) or cellular assays, (3) presence or absence of empty vector capsids, (4) age of the patient 65 , 126 and longitudinal studies in the same population over time, 63 (5) underlying disease, 62 , 63 , 65 , 126 and (6) vector manufacturing. Some candidates may also test positive for more than one serotype at a time.…”
Section: Aav-based Gene Therapy: the Quandariesmentioning
confidence: 99%
“…Overall, 20–40% of candidates for intravascular AAV gene therapy are not eligible due to the presence of NAbs to the vector capsid resulting from cross-reactivity after natural exposure to WT-AAV. 125 To date, it has been challenging to compare the efficacy of a given serotype across distinct studies due to a lack of normalization of the assays as most are developed “in house.” Potential modifiers of the rates/titers of NAbs could include (1) reporter gene, (2) assay technique whether neutralizing assays, non-neutralizing antibody assays (ELISA) or cellular assays, (3) presence or absence of empty vector capsids, (4) age of the patient 65 , 126 and longitudinal studies in the same population over time, 63 (5) underlying disease, 62 , 63 , 65 , 126 and (6) vector manufacturing. Some candidates may also test positive for more than one serotype at a time.…”
Section: Aav-based Gene Therapy: the Quandariesmentioning
confidence: 99%
“… 13 , 14 Screening adult CNs type 1 patients showed that 30.6% were not eligible for AAV-mediated gene therapy because of preexisting NAbs toward AAV8. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, depending on the vector production method and purification scheme, the final vector preparations can also contain empty viral particles, particles with truncated vector genomes or particles with plasmid or genomic DNA. All of those particles are essentially inactive virus, and their presence in an NAb assay will artificially lower the NAb titer ( 17 ). It is also noteworthy to point out that so-called “neutralizing antibody assays” also incorporate inhibition by other factors in the serum [e.g., galectin-3 binding protein ( 18 )] that inhibit transduction.…”
Section: Assays Measuring Neutralizing and Total Anti-aav Antibody Lementioning
confidence: 99%